2010
DOI: 10.1093/nar/gkq642
|View full text |Cite
|
Sign up to set email alerts
|

The ends of a large RNA molecule are necessarily close

Abstract: We show on general theoretical grounds that the two ends of single-stranded (ss) RNA molecules (consisting of roughly equal proportions of A, C, G and U) are necessarily close together, largely independent of their length and sequence. This is demonstrated to be a direct consequence of two generic properties of the equilibrium secondary structures, namely that the average proportion of bases in pairs is ∼60% and that the average duplex length is ∼4. Based on mfold and Vienna computations on large numbers of ss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 28 publications
(48 reference statements)
9
65
0
Order By: Relevance
“…We also showed that the expected 5 0 -3 0 distance is bounded by a constant that does not depend on the sequence length. As already mentioned, this phenomenon was proved by Clote for the homopolymer model and for structures with stickiness p [19], and it has been experimentally observed for the thermodynamic model [98].…”
Section: Secondary Structures As Scfgs: Asymptotics Prediction Homosupporting
confidence: 55%
“…We also showed that the expected 5 0 -3 0 distance is bounded by a constant that does not depend on the sequence length. As already mentioned, this phenomenon was proved by Clote for the homopolymer model and for structures with stickiness p [19], and it has been experimentally observed for the thermodynamic model [98].…”
Section: Secondary Structures As Scfgs: Asymptotics Prediction Homosupporting
confidence: 55%
“…In the RSPP of f¼0.6 (or f eff ¼0.27), the expected end-to-end distance, /XS % 12:0,14:4, and 24:9, for N¼500, 1000, and 10 000. Yoffe et al (2011) have also shown that for tymovirus, with a viral RNA of N ¼6300 and an unusually low pairing fraction of f¼0.45, the end-to-end distance is considerably higher at 26 7 5. The prediction of RSPP that /XS increases as f decreases agrees qualitatively with that findings.…”
Section: Discussionmentioning
confidence: 90%
“…The RSPP is a very simple and extremely approximate model to explain the end-to-end proximity of RNA molecules. Yoffe et al (2011) have demonstrated that the end-toend distance of RNAs approaches an asymptotic value of 12 7 5 for RNA of N Z 500. In the RSPP of f¼0.6 (or f eff ¼0.27), the expected end-to-end distance, /XS % 12:0,14:4, and 24:9, for N¼500, 1000, and 10 000.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…62,63 Although the mutation rate of microsatellites (i.e., AC repeats) in fish corresponds to that in mammals, the mutation in fish often causes gain or loss of multiple repeats whereas it rarely does in mammals. 62,64,65 Given this bias toward creating short blocks of AC or GT repeats, it is possible to see how a hairpin that bridges introns could arise or be destroyed by a single mutational event. However, we have shown that the bridging efficiency plateaus at 6 repeats, which may explain how its function is preserved even with high mutation rates.…”
Section: Rna Structures In Evolutionmentioning
confidence: 99%